2017
DOI: 10.3389/fpls.2017.00699
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Niches for Short-Season Grain Legumes in Semi-Arid Eastern Kenya — Coping with the Impacts of Climate Variability

Abstract: Climate variability is the major risk to agricultural production in semi-arid agroecosystems and the key challenge to sustain farm livelihoods for the 500 million people who inhabit these areas worldwide. Short-season grain legumes have great potential to address this challenge and help to design more resilient and productive farming systems. However, grain legumes display a great diversity and differ widely in growth, development, and resource use efficiency. Three contrasting short season grain legumes commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Teixeira et al (2015), using APSIM, demonstrated the importance of rotations for simulating climate impact assessments and Sennhenn et al (2017) found new niches for short season legumes in Kenya. APSIM has been used in simulation studies for yield gap assessment in legumes such as soybean, groundnut, pigeonpea, and chickpea in India (Bhatia et al, 2007;Chauhan et al, 2008), in simulation of soil temperature in the podding zone of groundnut (Chauhan et al, 2007), and in assessment of the impacts of fertilizers and legumes on N 2 O and CO 2 emissions from soils in subtropical agricultural systems (Huth et al, 2010).…”
Section: Crop Growth Simulation and Modelling Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Teixeira et al (2015), using APSIM, demonstrated the importance of rotations for simulating climate impact assessments and Sennhenn et al (2017) found new niches for short season legumes in Kenya. APSIM has been used in simulation studies for yield gap assessment in legumes such as soybean, groundnut, pigeonpea, and chickpea in India (Bhatia et al, 2007;Chauhan et al, 2008), in simulation of soil temperature in the podding zone of groundnut (Chauhan et al, 2007), and in assessment of the impacts of fertilizers and legumes on N 2 O and CO 2 emissions from soils in subtropical agricultural systems (Huth et al, 2010).…”
Section: Crop Growth Simulation and Modelling Approachesmentioning
confidence: 99%
“…As a result, the genetic gain achieved is about 1% per year in several species (Duvick, 2005;Cooper et al, 2009;Brisson et al, 2010;Lopes et al, 2012;Aisawi et al, 2015). The most promising option to design more drought resilient and sustainable production is to target the major traits of adaptation that include early flowering and seed set before the onset of terminal drought (Sennhenn et al, 2017).…”
Section: Genomics-assisted Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that yield losses for early to medium maturing sorghum cultivars may not be associated to erratic rainfall pattern but rather lack of nitrogen in the soil because the physiological potential of the cultivars falls within received in-season rainfall. It is, however, expected that the increase temperature might have a more severe impacts on sorghum productivity as it accelerates vegetative growth and maturity processes irrespective of whether rainfall increases or decreases in the semiarid area (Sultan et al 2014;Sennhenn et al 2017). Furthermore, the analysis of variance (ANOVA) indicates that simulated grain yield and total biomass were highly significant (p < .001) due to N-application rates and cultivars while significant interaction of N-rate and cultivar (N Â C) existed only for grain yield and total biomass in Kano and total biomass in Samaru (Table 5).…”
Section: Grain Yield Total Biomass and Water Use Efficiency Under DImentioning
confidence: 99%
“…Most of this crop production is characterized by limited application of inputs (due to the high cost and limited availability of agricultural inputs including seeds, fertilizers and agricultural chemicals), *Corresponding author. E-mail: M_entz@umanitoba.ca Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License deteriorating soil conditions (Vagen et al, 2005) and increasingly uncertain weather patterns (Sennhenn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%